Effect of the Direct Renin Inhibitor Aliskiren on Urinary Albumin Excretion in Spontaneous Type 2 Diabetic KK-Ay Mouse. (2nd June 2013) - Furukawa, Masako; Gohda, Tomohito; Hagiwara, Shinji; Tanimoto, Mitsuo; Horikoshi, Satoshi; Funabiki, Kazuhiko; Tomino, Yasuhiko
Abstract : Objective . Although angiotensin II-mediated inflammation and extracellular matrix accumulation are considered to be associated with the progression of diabetic nephropathy, these processes have not yet been sufficiently clarified. The objective of this study was to determine whether the correction of the abnormal renal expression of MMPs and its inhibitors (MMPs/TIMPs) and cytokines following the administration of aliskiren to KK-A y mice results in a renoprotective effect. Methods . KK-A y mice were divided into two groups, that is, untreated (saline) and treated (aliskiren) groups. Systolic BP, HbA1c levels, and the albumin-creatinine ratio (ACR) were measured. The renal expression of MMPs/TIMPs, fibronectin, type IV collagen, MCP-1, and (pro)renin receptor ((P)RR) was examined using real-time PCR and/or immunohistochemical staining. Renal MAPK and NF- κ B activity were also examined by Western blot analyses and ELISA, respectively. Results . Significant decreases in systolic BP and ACR levels were observed in treated KK-A y mice compared with the findings in untreated KK-A y mice. Furthermore, increases in MMPs/TIMPs, fibronectin, type IV collagen, MCP-1, and (P)RR expression, in addition to MAPK and NF- κ B activity, were significantly attenuated by aliskiren administration. Conclusions . It appears that aliskiren improves albuminuria and renal fibrosis by regulating inflammation and the alteration of collagen synthesis and degradation.